Unravelling faradaic electrochemical efficiencies over Fe/Co spinel metal oxides using surface spectroscopy and microscopy techniques - Kashyap, Varchaswal; Pandikassala, Ajmal; Singla, Gourav; Khan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P.; Kurungot, Sreekumar (Nanoscale, 2022)
Cobalt and iron metal-based oxide catalysts play a significant role in energy devices. To unravel some interesting parameters, we have synthesized metal oxides of cobalt and iron (i.e. Fe2O3, Co3O4, Co2FeO4 and CoFe2O4), and measured the effect of the valence band structure, morphology, size and defects in the nanoparticles towards the electrocatalytic hydrogen evolution reaction (HER), the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). The compositional variations in the cobalt and iron precursors significantly alter the particle size from 60 to <10 nm and simultaneously the shape of the particles (cubic and spherical). The Tauc plot obtained from the solution phase ultraviolet (UV) spectra of the nanoparticles showed band gaps of 2.2, 2.3, 2.5 and 2.8 eV for Fe2O3, Co3O4, Co2FeO4 and CoFe2O4, respectively. Further, the valence band structure and work function analysis using ultraviolet photoelectron spectroscopy (UPS) and core level X-ray photoelectron spectroscopy (XPS) analyses provided better structural insight into metal oxide catalysts. In the Co3O4 system, the valence band structure favors the HER and Fe2O3 favors the OER. The composites Co2FeO4 and CoFe2O4 show a significant change in their core level (O 1s, Co 2p and Fe 2p spectra) and valence band structure. Co3O4 shows an overpotential of 370 mV against 416 mV for Fe2O3 at a current density of 2 mA cm(-2) for the HER. Similarly, Fe2O3 shows an overpotential of 410 mV against the 435 mV for Co3O4 at a current density of 10 mA cm(-2) for the OER. However, for the ORR, Co3O4 shows 70 mV improvement in the half-wave potential against Fe2O3. The composites (Co2FeO4 and CoFe2O4) display better performance compared to their respective parent oxide systems (i.e., Co3O4 and Fe2O3, respectively) in terms of the ORR half-wave potential, which can be attributed to the presence of the oxygen vacancies over the surface in these systems. This was further corroborated in density functional theory (DFT) simulations, wherein the oxygen vacancy formation on the surface of CoFe2O4(001) was calculated to be significantly lower (similar to 50 kJ mol(-1)) compared to Co3O4 (001). The band diagram of the nanoparticles constructed from the various spectroscopic measurements with work function and band gap provides in-depth understanding of the electrocatalytic process.